Participation of traditional leadership on spatial planning and land use management matters in the Mpumalanga province Republic of South Africa - Nkosi, Simanga Acron (University of the Free State, 2016)
This research report explores the participation of traditional leadership in spatial planning and land use management matters in Mpumalanga Province. The report provides a brief overview of the historic background of traditional leadership in South Africa and the applicable legislation that outlines the mandates and the roles of traditional leadership on land matters. The compilation of the mini-dissertation from inception to conclusion is driven by data resources on traditional leadership guided by the following measures: literature review, which entails defining traditional leaders and their existence through the epoch in history, policy framework, as well as history and theory of planning. Information collected from traditional leaders and municipal officials was analysed to provide outcomes of the survey which was compared with the literature outcome to provide a final outcome which presents a final view of the extent of participation of traditional leadership in spatial planning and land use management. The finding of the report indicates that systems of traditional leadership are alive and existing in rural areas of South Africa and that the institution of traditional leadership will still exist in the coming future. Their involvement in land matters is inherited from the past, therefore their current role in spatial planning and land use management must be defined and agreed between the traditional council and municipalities and finally the agreements must be documented in a form of a Service Level Agreement.
Keywords: Land use, Urban -- South Africa -- Mpumalanga; Spatial behavior -- South Africa -- Mpumalanga; Dissertation (M.U.R.P. (Urban and Regional Planning))--University of the Free State, 2016